Andreou, Christos - (:unkn) unknown (My University, 2026)
Christos Andreou is a Senior Nursing Officer and currently works as nurse educator in the Nursing Department, Faculty of Health Sciences at Cyprus University of Technology. He received his PhD on the exploration of individual learning styles and critical thinking among undergraduate nursing students as well as the relationships between those variables. His degrees also include Master of Atrium on Health Services Management, Bachelor of Science (Hons) on Nursing and Diploma on Nursing Administration. He served as a clinical nurse for 8 years in Surgical, Urological and Intensive Care Unit. He has been the Chief Editor of the national scientific journal Cyprus Nursing Chronicles 2000 - 2015. He served as General Secretary and a member of the Cyprus Nurses and Midwives Association Board of Directors for the period 2000-2015 and as a member of the National Bioethics Committee for the period 2011-2015. He currently serves as a member of the National Review Bioethics Committee for Biomedical Research on Human Being and their biological substances and the clinical trials on Medicinal Products of Human Use. His main research areas concern the theory-practice gap in Nursing and topics related on teaching, learning and critical thinking development within undergraduate nursing education. He has published articles at national and international level related with the concept of critical thinking in Nursing, the individual learning styles, the critical thinking and its relationship in baccalaureate nursing education as well as a complete methodological study on the adaptation and the validation of the Learning Style Inventory in Greek language. His current focus on research topics is directed towards the potential optimization of the learning achievements and the critical thinking development among undergraduate nursing students.
Keywords: Learning Style Inventory; Registered Nurse Forecasting (RN4CAST); Nursing Psychology; Nurse-Patient Relations